Conversations with people who hate me : 12 things I learned from talking to Internet strangers - Marron, Dylan, 1988- (Atria Books, 2022)
From the host of the award-winning, critically acclaimed podcast Conversations with People Who Hate Me comes a thought-provoking, witty, and inspirational exploration of difficult conversations and how to navigate them.